2022
DOI: 10.1108/hff-02-2022-0128
|View full text |Cite
|
Sign up to set email alerts
|

The aerodynamic effects of blade pitch angle on small horizontal axis wind turbines

Abstract: Purpose The purpose of this paper is to thoroughly investigate the aerodynamic effects of blade pitch angle on small scaled horizontal axis wind turbines (HAWTs) using computational fluid dynamics (CFD) method to find out the sophisticated effects on the flow phenomena and power performance. Design/methodology/approach A small HAWT is used as a reference to validate the model and examine the aerodynamic effects. The blade pitch angle was varied between +2 and −6 degrees, angles which are critical for the ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
(17 reference statements)
0
2
0
Order By: Relevance
“… 74 , 75 , 76 , 77 As research on small horizontal rotors advanced, the significance of pitch angle was discovered. 78 , 79 , 80 Mayer et al. 81 analyzed how different pitch angles impacted small horizontal rotor starting performance.…”
Section: Wind Energy Rectifiersmentioning
confidence: 99%
“… 74 , 75 , 76 , 77 As research on small horizontal rotors advanced, the significance of pitch angle was discovered. 78 , 79 , 80 Mayer et al. 81 analyzed how different pitch angles impacted small horizontal rotor starting performance.…”
Section: Wind Energy Rectifiersmentioning
confidence: 99%
“…Although the blade pitch angle can affect the performance of a HAWT, its effect may be weaker than those of the airfoil and angle of attack. Kaya et al [24] numerically studied the aerodynamic effects of the blade pitch angle on the performance of small HAWTs at different TSRs. Their results indicated that at low TSRs, a more downward blade pitch angle resulted in a higher C P and a smaller thrust coefficient (C T ); however, at high TSRs, the effect of the blade pitch angle on C P was the reverse.…”
Section: Introductionmentioning
confidence: 99%